Photocatalytic degradation of aqueous organic solvents in the presence of hydroxyl radical scavengers - Mehrab Mehrvar; William A. Anderson; Murray Moo-Young (International Journal of Photoenergy)
Tetrahydrofuran (THF) and 1,4-dioxane (DIOX) are two common solvents that are found in contaminated groundwater. Photocatalytic degradation of these two organic solvents in water was studied in the presence of carbonate and bicarbonate, which are hydroxyl radical scavengers. The reactions were performed in an annular slurry photoreactor. It was found that bicarbonate and carbonate ions acted as hydroxyl radical scavengers and slowed down the DIOX degradation rate but did not significantly affect the THF degradation rate. The slight enhancement in the THF degradation rate in the presence of sodium bicarbonate may be due to the increase in pH. In addition, it appears that bicarbonate and carbonate ions were reduced to other organic species during the photocatalytic reaction.